Estudo sobre as transformações nas tipologias arquitetônicas em conjuntos habitacionais de interesse social em Fortaleza-CE: 2003-2012. - Vieira, Geovana Alves Rocha (2013)
The housing deficit reaches Brazil since the late nineteenth century when starting an accelerated process of city growth associated with rapid population growth and insufficient implementation of urban infrastructure. Faced with this problem several policies have been formulated in order to meet the growing demand for housing and promote the orderly growth of our cities. However the need to cover a huge number of people makes the preparation of projects is based in the resolution quantitative this deficit even if it interferes with their quality. In this context this research aims to analyze the architectural projects intended for social housing (SH) in capital of Ceará produced by Municipal Prefecture through the Foundation Housing Development in Fortaleza (HABITAFOR) from 2003 the year of creation of the institution cited to 2012. This research adopts as a research strategy the document analysis by performing four steps: collection of architectural projects in the institution responsible and the organization of the material collected appreciation of documents through the analysis parameters developed and soon thereafter treatment of same. The analysis shows that the designs produced by Habitafor mostly are intended to resettle families living in areas at risk. It was found also that the architectural projects have three sectors: social intimate and service a common characteristic in the Brazilian housing but not in all architectural projects have this zoning and that increasing the number of rooms does not imply an extension the other spaces. The projects analyzed are inflexible because the plants analyzed do not favor the expansion of the units according to the needs of families